2016
DOI: 10.3389/fmicb.2016.01564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes during Bacillus subtilis Spore Outgrowth in High-Salinity Environments Using RNA Sequencing

Abstract: In its natural habitat, the soil bacterium Bacillus subtilis often has to cope with fluctuating osmolality and nutrient availability. Upon nutrient depletion it can form dormant spores, which can revive to form vegetative cells when nutrients become available again. While the effects of salt stress on spore germination have been analyzed previously, detailed knowledge on the salt stress response during the subsequent outgrowth phase is lacking. In this study, we investigated the changes in gene expression duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 77 publications
1
38
1
1
Order By: Relevance
“…Therefore, our research was fully focused on 2-day exposure to salt stress. In pure-culture transcriptome studies, this exposure time is considered long-term incubation given that microorganisms that are able to cope with moderate and high salt stress exhibit an adaptive transcriptome response within 2 days (Zaprasis et al, 2015; Nagler et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our research was fully focused on 2-day exposure to salt stress. In pure-culture transcriptome studies, this exposure time is considered long-term incubation given that microorganisms that are able to cope with moderate and high salt stress exhibit an adaptive transcriptome response within 2 days (Zaprasis et al, 2015; Nagler et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Depending on the ability of the particular microorganism to cope with salt stress, this early period is followed by an adaptive transcriptome response that is governed by up-regulation of gene expression. This adaptive response occurs within a few hours or days (Zaprasis et al, 2015; Nagler et al, 2016). The key taxonomic groups involved in the methanogenic breakdown of plant polymers significantly differed in their ability to cope with salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins belong to the ABC transporters family, including the protein and amino acid transporters, as well as families of ion transporters. Interestingly, in a recent transcriptome study, almost 80 transcripts encoding different transporters have been identified from spore mRNA isolates 23 .…”
Section: Other Transportersmentioning
confidence: 99%
“…2G). RNA is extracted from germinated spores or outgrowing cells over time and analyzed using different methods such as microarrays (Keijser et al, 2007), RNA-seq (Nagler et al, 2016) or RT qPCR (Bassi et al, 2016). Gene expression can be analyzed by specific pipelines such as T-Rex or JBrowse (Skinner, Uzilov, Stein, Mungall, & Holmes, 2009;de Jong, van der Meulen, Kuipers, & Kok, 2015).…”
Section: Molecular Methods (Fig 2e-f-g)mentioning
confidence: 99%